Penerapan Metode SAW dalam Menentukan Perangkat Desa Guworejo Terbaik (Kasus: Kantor Desa Guworejo) - Pangestu, Galang Aji; Mariana, Novita (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The village apparatus is part of the government element at the village level whose task is to assist the village head in carrying out government duties at the village level. Guworejo village officials are located in Karangmalang District, Sragen Regency. In carrying out their duties, village officials are required to have a humane nature to the whole community. So it takes appreciation of village officials who have a high work spirit and responsibility. To determine the best village apparatus, the Guworejo village government is still not optimal, this is due to the absence of media that can process the assessment of the apparatus and determine the best village apparatus. Therefore, this research is expected to help the Guworejo village government in determining the best village apparatus. In this study, the SAW (Simple Additive Weighting) method will be used. The basic concept of the SAW method is to find the weighted sum of the performance ratings on each alternative on all attributes.